2019
DOI: 10.22270/ajprd.v7i6.631
|View full text |Cite
|
Sign up to set email alerts
|

The Potency of Artocarpus Heterophyllus Leaf as a Facial Skin Care Ingredient in Clay Mask Formulation

Abstract: Artocarpus heterophyllus (Ah), common name as nangka,  has been reported to have antidiabetic, antihyperlipidemia, antimicrobial and antioxidant activity. Balinese women used its leaves for facial treatment. This study aims to evaluate its leaf potency for facial skin care. Ethanol extract of Ah (EEAh) that obtained by maceration was prepared into 3 clay mask formulations (FI: 1%, FII:3% and FIII:5%). F0 was used as control group. A total of 12 volunteers were treated with clay mask to evaluate its effect on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…These chemical constituents are responsible for their pharmacological activities. The previous study demonstrated its leaves effect that benefits facial skincare by improving moisture, smoothness, pore size, blemishes, and wrinkles ( 4 - 6 )…”
Section: Introductionmentioning
confidence: 99%
“…These chemical constituents are responsible for their pharmacological activities. The previous study demonstrated its leaves effect that benefits facial skincare by improving moisture, smoothness, pore size, blemishes, and wrinkles ( 4 - 6 )…”
Section: Introductionmentioning
confidence: 99%